The prognostic value of pretreatment neutrophil-lymphocyte ratio and platelet-lymphocyte ratio in patients with esophageal cancer undergoing immunotherapy: a systematic review and meta-analysis - Deng, Min; Qing, Yun; Qiu, Dan; Sheng, Ya; Zhou, Juan; Sun, Lan (Frontiers in Oncology, 2025)
BackgroundEsophageal cancer (EC) is associated with a high morbidity and mortality rate. Immunotherapy has demonstrated effective antitumor activity in patients with EC, making it imperative to investigate easily accessible prognostic factors. Consequently, we conducted a meta-analysis to explore the prognostic significance of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in EC patients treated with immunotherapy.MethodsThe literature search was conducted across three databases: PubMed, Embase, and Web of Science. The primary deadline for literature retrieval was July 2024. Hazard ratio (HR) with a 95% confidence interval (CI) was utilized to assess the association between NLR or PLR and overall survival (OS) as well as progression-free survival (PFS). Statistical analysis was performed using Review Manager version 5.4 and STATA version 15.0.ResultsThe meta-analysis included a total of 16 studies involving 1,481 patients. The results indicated a significant correlation between high pretreatment NLR and poor PFS (HR=1.76, 95%CI:1.38-2.25, p<0.001) as well as poor OS (HR=2.61,95%CI:1.86-3.67, p<0.001). Subgroup analyses based on tumor stage revealed that the association between elevated NLR and poor PFS was only observed in advanced EC patients. Regarding PLR, an increased PLR was found to be indicative of inferior PFS (HR=1.44, 95%CI: 1.20-1.72, p<0.001) and OS (HR=1.72,95%CI:1.08-2.74, p=0.020). However, the sensitivity analyses suggested that the observed increase in PLR lack robustness in terms of its impact on inferior OS.ConclusionElevated NLR and PLR are associated with inferior PFS and OS in EC patients receiving immunotherapy. These findings suggest that NLR and PLR levels hold promise as prognostic biomarkers in clinical practice, offering valuable guidance for personalized immunotherapy strategies.Systematic Review RegistrationPROSPERO https://www.crd.york.ac.uk/prospero/, identifier CRD42024596737.